Development of the Reed Industry Group Through Training in Financial Management, Management and Sustainable Architectural Building Design - DEWI, Kadek Goldina Puteri; WAHYUNI, Ni Made; ARTHA, Pande Putu Dwi Novigga (Indonesia Strategic Sustainability, 2024)
Industry plays a vital role in reducing poverty in developing countries. In Bali, the creative industry has developed rapidly, although initially, it was still small. The alang-alang roofing industry, which focuses on producing and using roofing from alang-alang leaves, is a significant sector in the construction and property development industry. This material is used in traditional buildings and modern, environmentally friendly building designs. A case study of the